Organization of investment activity of industrial enterprises (Путеводитель предпринимателя)
This article discusses current issues investment industry. The investments of the industry -is not only tactical and strategic objective. With its decision to link the problem of development of new industrial technologies, sustainable development of the industry, employment and living standards, economic growth, socio-economic stability and public safety.